STRUCTURAL CHANGES IN THE BRAIN OF RATS WITH EXPERIMENTAL ALLERGIC ENCEPHALOMYELITIS AFTER CRYOPRESERVED MESENCHYMAL STEM CELLS IMPACT - Semenova, V.M.; Tsymbalyuk, V.I.; Liubich, L.D.; Egorova, D.M.; Stayno, L.P.; Shevchuk, O.V.; Vaslovich, V.V.; Verbovska, S.A.; Deryabina, O.G.; Shuvalova, N.S.; Pichkur, L.D. (World of Medicine and Biology, 2020)
In the chronic course of experimental allergic encephalomyelitis neurodegenerative changes in the brain tissue of rats exacerbate within 2 months. Suboccipital administration of mesenchymal stem cells obtained from human umbilical cord (1×106) and cryopreserved in the solution containing 3% dimethyl sulfoxide, 15% ethylene glycol, 10% sucrose, 12% trehalose, and 60% fetal calf serum inhibits these changes in hippocampus (day 35); administration of those cryopreserved in the solution containing 4% dimethyl sulfoxide, 6% trehalose, and 90% fetal calf serum inhibits these changes in both hippocampus (days 35-60) and brain cortex (day 60); administration of these cells cryopreserved in the solution containing 10% dimethyl sulfoxide and 90% fetal calf serum slows down the changes in hippocampus (days 35-60) and partly recover the neuronal component in the brain cortex (day 60).